End-stage renal disease and low level exposure to lead, cadmium and mercury; a population-based, prospective nested case-referent study in Sweden - Sommar Johan Nilsson; Svensson Maria K; Björ Bodil M; Elmståhl Sölve I; Hallmans Göran; Lundh Thomas; Schön Staffan MI; Skerfving Staffan; Bergdahl Ingvar A (BMC, 2013)
Abstract Background Cadmium (Cd), lead (Pb), and mercury (Hg) cause toxicological renal effects, but the clinical relevance at low-level exposures in general populations is unclear. The objective of this study is to assess the risk of developing end-stage renal disease in relation to Cd, Pb, and Hg exposure. Methods A total of 118 cases who later in life developed end-stage renal disease, and 378 matched (sex, age, area, and time of blood sampling) referents were identified among participants in two population-based prospective cohorts (130,000 individuals). Cd, Pb, and Hg concentrations were determined in prospectively collected samples. Results Erythrocyte lead was associated with an increased risk of developing end-stage renal disease (mean in cases 76 μg/L; odds ratio (OR) 1.54 for an interquartile range increase, 95% confidence interval (CI) 1.18-2.00), while erythrocyte mercury was negatively associated (2.4 μg/L; OR 0.75 for an interquartile range increase, CI 0.56-0.99). For erythrocyte cadmium, the OR of developing end-stage renal disease was 1.15 for an interquartile range increase (CI 0.99-1.34; mean Ery-Cd among cases: 1.3 μg/L). The associations for erythrocyte lead and erythrocyte mercury, but not for erythrocyte cadmium, remained after adjusting for the other two metals, smoking, BMI, diabetes, and hypertension. Gender-specific analyses showed that men carried almost all of the erythrocyte lead and erythrocyte cadmium associated risks. Conclusions Erythrocyte lead is associated with end-stage renal disease but further studies are needed to evaluate causality. Gender-specific analyses suggest potential differences in susceptibility or in exposure biomarker reliability.